Sputtering Physical Vapour Deposition (PVD) Coatings: A Critical Review on Process Improvement and Market Trend Demands - Baptista, Andresa (2020)
Physical vapour deposition (PVD) is a well-known technology that is widely used for the deposition of thin films regarding many demands, namely tribological behaviour improvement, optical enhancement, visual/esthetic upgrading, and many other fields, with a wide range of applications already being perfectly established. Machining tools are, probably, one of the most common applications of this deposition technique, sometimes used together with chemical vapour deposition (CVD) in order to increase their lifespan, decreasing friction, and improving thermal properties. However, the CVD process is carried out at higher temperatures, inducing higher stresses in the coatings and substrate, being used essentially only when the required coating needs to be deposited using this process. In order to improve this technique, several studies have been carried out optimizing the PVD technique by increasing plasma ionization, decreasing dark areas (zones where there is no deposition into the reactor), improving targets use, enhancing atomic bombardment efficiency, or even increasing the deposition rate and optimizing the selection of gases. These studies reveal a huge potential in changing parameters to improve thin film quality, increasing as well the adhesion to the substrate. However, the process of improving energy efficiency regarding the industrial context has not been studied as deeply as required. This study aims to proceed to a review regarding the improvements already studied in order to optimize the sputtering PVD process, trying to relate these improvements with the industrial requirements as a function of product development and market demand.